Prevalence of Schizophrenia in South Jakarta Administration City (Jurnal Ilmu Kesehatan Masyarakat, 2019)
Background: The population of DKI Jakarta is 10,377,186 people and it is estimated that in DKI Jakarta there are 11,415 cases of schizophrenia. Newly discovered, recorded and handled during 2017 were 4,690 cases. The prevalence of schizophrenia in DKI Jakarta in 2017 is 1.1 / 1000. This study aims to visualize descriptively the prevalence of schizophrenia in South Jakarta Administrative city. Methods: The method of study was cross sectional. The population of all schizophrenia cases obtained from the recording of medical records in 10 sub-district health centers during 2017 was 1,641 patients. Characteristics seen were gender, age, place of residence, patients treated at the health center and those referred to and regular treatment of schizophrenic patients. Results: The highest prevalence rate in Kebayoran Baru was 11.4/10,000, the largest proportion of 1,641 schizophrenia cases in South Jakarta Administrative City as much as 14% came from Tebet, the highest proportion of male sex was 73% in Tebet, the highest female in Mampang Prapatan by 45%, the proportion of schizophrenia cases was highest in the age 26-45 was 56%, the proportion of schizophrenia in Tebet treated in Puskesmas was 84%, referred to the Hospital as much as 16%, who were not regularly treated at the Puskesmas in 2017 was 56 %. Conclusion: The largest proportion of schizophrenia is at the age 26-45 in Cilandak Subdistrict, Cilandak Community Health Center handles schizophrenia more because early detection of mental disorders is better than other regions, Jagakarsa Health Center is further strengthened to handle schizophrenia cases.